2021
DOI: 10.14202/vetworld.2021.1014-1019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factors associated with owner's individual decision to vaccinate their dogs against rabies: A house-to-house survey in Ouagadougou, Burkina Faso

Abstract: Background and Aim: In rabies endemic area, dog vaccination is an effective way of controlling the disease in animals and humans if a minimum of 70% vaccination coverage is reached. This study aimed to identify dog demographics and household characteristics associated with dogs' vaccination against rabies in Ouagadougou, Burkina Faso. Materials and Methods: A questionnaire was used to collect data from respondents with regard to their dogs' demographics and their household characteristics. Chi-square test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Similarly, owners who had a family veterinary clinic, visited a veterinary clinic at least once every 6 months, and who had ever been advised to vaccinate their dog against rabies were more likely to vaccinate their dog against rabies. The identified factors were broadly consistent with findings about dog owner characteristics in other country settings [ 9 , 10 , 11 , 12 , 13 , 17 , 18 , 19 ]. While the total number of dogs is not available and thus it has been difficult to estimate the annual rabies vaccination coverage in dogs, we successfully obtained a sample estimate of the annual vaccination coverage against rabies in dogs and identified differences in the characteristics of dogs related to vaccination by the number of rabies vaccinations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, owners who had a family veterinary clinic, visited a veterinary clinic at least once every 6 months, and who had ever been advised to vaccinate their dog against rabies were more likely to vaccinate their dog against rabies. The identified factors were broadly consistent with findings about dog owner characteristics in other country settings [ 9 , 10 , 11 , 12 , 13 , 17 , 18 , 19 ]. While the total number of dogs is not available and thus it has been difficult to estimate the annual rabies vaccination coverage in dogs, we successfully obtained a sample estimate of the annual vaccination coverage against rabies in dogs and identified differences in the characteristics of dogs related to vaccination by the number of rabies vaccinations.…”
Section: Discussionsupporting
confidence: 84%
“…The characteristics of dog owners that are associated with rabies vaccination in dogs have been previously investigated, mainly in African countries. Regarding owner demographics, the following characteristics have been reported as positively associated with dog rabies vaccination: higher education level [ 9 , 10 , 11 , 12 , 13 ], older age [ 12 , 13 ], higher socioeconomic level [ 12 , 14 ], fewer people living in a household [ 10 , 15 ], having an occupation [ 9 , 10 , 12 , 13 ], being part of a religious group (Muslim) [ 9 ], living in an urban area [ 9 , 10 ], and having a private residence [ 11 ]. Other factors include knowledge about rabies [ 9 , 11 , 12 , 14 , 16 ], knowledge about the location of veterinary offices/clinics [ 11 ], the breed of dog (exotic/hybrid vs. local) [ 11 , 12 , 14 ], where the dog was obtained (purchased vs. given) [ 10 , 12 , 14 ], confinement status of the dog home (i.e., confined vs. free-roaming) [ 12 , 14 ], perception of the rabies vaccination cost [ 12 ], and providing veterinary care to owned dogs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, among the dog owners who failed to vaccinate their dogs, 44.6% thought vaccinating dogs too troublesome and 31.5% did not know where to vaccinate dogs. Similarly, some previous studies also suggested other factors such as a limited number of vaccinating sites and veterinarians, long distance to the sites and veterinary clinic, and feeling difficulty confining the dogs for vaccination would prevent many dog owners from accessing rabies vaccinations ( 6 - 7 ). Therefore, supporting conditions for relevant policies, such as veterinary systems and a free policy, are also important factors affecting dog vaccination against rabies.…”
Section: Discussionmentioning
confidence: 93%
“…Bite wounds are not allowed to be sutured except for situational sutures. When stitches are necessary, Anti-Rabies Serum (SAR) is given according to the dose, infiltrating around the wound, and the rest is injected intra-muscularly (16). Furthermore, administering anti-tetanus serum/vaccine, antibiotics to prevent infection, and analgesics should also be considered.…”
Section: Discussionmentioning
confidence: 99%